Physical manifestations of ungrammaticality - Plattner, Silvan (Kansas State University, 2023)
This study investigates the processing and perception of German gender agreement by non-native speakers. Specifically, this study seeks to gather information on physical discomfort felt by non-native speakers when confronted with violations in gender agreement in German. The variables examined are the frequency of the lexical items (high or low frequency), modality (reading silently versus out loud), and grammaticality (correct or incorrect). The results suggest that L2 German learners at an intermediate proficiency level can experience physical discomfort when confronted with ungrammatical language like native speakers. Furthermore, the data suggests that non-native speakers are more likely to notice violations in gender agreement when speaking out loud, and that the physical discomfort is stronger with more familiar lexical items. The data from this study is the first of its kind, offering insight into how language modality affects grammaticality judgments in the second language. With less frequent lexical terms participants expressed another sense of discomfort related to uncertainty. This feeling presented itself differently from the physical discomfort felt when confronted with violations of gender agreement.
Keywords: Linguistics; Language pedagogy; Grammaticality judgment task